Apoptosis drives cancer cells proliferate and metastasize. Issue 1 (11th January 2013) - Wang, Rui‐An; Li, Qin‐Long; Li, Zeng‐Shan; Zheng, Ping‐Ju; Zhang, Hui‐Zhong; Huang, Xiao‐Feng; Chi, Su‐Min; Yang, An‐Gang; Cui, Rutao
Abstract Cancer has been considered to be the result of accumulated gene mutations, which result in uncontrolled cell proliferations for a long time. Cancers are also regarded to be capable of immune evasion. Furthermore, resistance to apoptosis was recognized as an important trait of cancer in the last score of years. However, there are numerous paradoxical issues in this whole set of theory. For example, there is no known set of genes of which mutations are responsible for human cancers. As for the trait of 'resistance to apoptosis', the fact is that cancer has increased frequency of apoptosis. The more malignant the tumour is, the more apoptosis shows. In this study, we propose a new theory that apoptosis plays a key role in the malignant progression and metastasis of cancer. The growth of tumour is the difference between tumour cell proliferation and attrition plus the hyperplastic growth of stroma. Increased and unpreventable death caused by innate or environmental factors such as ischaemia and inflammation drives the tumour cells to proliferate relentlessly, move to new lands to establish colonies. In short, increased cell death is the origin of malignancy.